Comprehensive mapping of NICU developmental care nursing interventions and related sensitive outcome indicators: a scoping review protocol. Issue 1 (31st January 2022) - Héon, Marjolaine; Aita, Marilyn; Lavallée, Andréane; De Clifford-Faugère, Gwenaëlle; Laporte, Geneviève; Boisvert, Annie; Feeley, Nancy
Abstract : Introduction: Neurodevelopmental outcomes of preterm infant are still a contemporary concern. To counter the detrimental effects resulting from the hospitalisation in the neonatal intensive care unit (NICU), developmental care (DC) interventions have emerged as a philosophy of care aimed at protecting and enhancing preterm infant's development and promoting parental outcomes. In the past two decades, many authors have suggested DC models, core measures, practice guidelines and standards of care but outlined different groupings of interventions rather than specific interventions that can be used in NICU clinical practice. Moreover, as these DC interventions are mostly implemented by neonatal nurses, it would be strategic and valuable to identify specific outcome indicators to make visible the contribution of NICU nurses to DC. Objectives: The overarching objective of this review is to identify the nature, range, and extent of the literature regarding DC nursing interventions for preterm infants in the NICU. The secondary twofold objectives are to highlight interventions that fall into identified categories of DC interventions and suggest nursing-sensitive outcome indicators related to DC interventions in the NICU. Inclusion criteria: Papers reporting on or discussing a DC nursing intervention during NICU hospitalisation will be included. Methods and analysis: The Joanna Briggs Institute's methodology for scoping reviews will be followed. CINAHL, MEDLINE, Embase, PubMed, Web of Science, Scopus, ProQuest and PsycInfo databases from 2009 to the present will be searched. Any type of paper, published in English or French, will be considered. Study selection and data extraction will be conducted by pairs of two review authors independently. A qualitative content analysis will be conducted. Ethics and dissemination: No Institutional Review Board ethical approbation is needed. Results of this review will be presented in scientific meetings and published in refereed papers.